The relationship between flat foot and Q-angle in elementary school students - Dewa Gede Gangga Kusuma Putra; I Putu Yudi Pramana Putra; Ni Luh Putu Gita Karunia Saraswati; Anak Ayu Nyoman Trisna Narta Dewi (Physical Therapy Journal of Indonesia, 2023)
Background: Elementary school students have unique characteristics. Each child has their ways of doing their activities. In its activities, of course, there are risks, especially in the lower extremities, namely flat foot, which is the condition of the medial arch treading with the ground or flat due to emphasis on the medial part, excessive or over foot conditions will result in an increase in valgus shape in the knee joint; thus the degree of quadriceps angle (Q-angle) can increase. This study aims to determine the relationship between flat foot and Q-angle in elementary school children in Kusamba Village, Dawan District, Klungkung Regency. Objective: This study aims to determine the relationship between flat feet and Q-angle. Methods: Observational analytical cross-sectional design that uses simple random sampling techniques with a sample of 51 people according to predetermined inclusion and exclusion criteria. Data were collected with a wet footprint test and Clark's angle to find a flat foot and Q-angle with a 360o goniometer. Results: The analysis test results obtained a result of p=0.000 (p<0.05), so it can be explained that there is a significant relationship between flat foot and Q-angle. The results of the spearmen-rho analysis obtained a moderate relationship with the value of the correlation coefficient on the right flat foot with a right Q-angle of 0.527 and the left flat foot with a left Q-angle of 0.597 which means the direction of the relationship is unidirectional. Conclusion: Based on the study's results, it can be concluded that there is a moderate, unidirectional, and meaningful relationship between flat foot and Q-angle in elementary school children in Kusamba Village, Dawan District, Klungkung Regency.